English Language Teaching Online Class During Covid-19 Era - Muhammad Dalimunthe; Sholihatul Hamidah Daulay; Surya Wijaya Purnama (Universitas Pahlawan Tuanku Tambusai, 2022)
Online learning is a transitional form of the education system in the era of the Covid-19 pandemic. This is attempted as a form of continuing education by utilizing the Zoom, WhatsApp (WA), Google Form, and Google Meet applications. This study attempts to describe English learning activities at SMP IT Ad-Durrah Medan which implements an online learning system via WhatsApp. The data collection process was carried out systematically using interview techniques (also via online via google form). The results of this study indicate that online learning systems are considered appropriate as an alternative to maintaining the sustainability of the educational process in the Covid-19 era, including those practiced by education providers at SMP IT Ad-Durrah Medan. The reason for using the WhatsApp application is based on the familiarity of the application among teachers, students, and student guardians. The process of learning activities, assignments, and learning assessments are carried out virtually by educators during the Covid-19 pandemic. Likewise, the weaknesses of the online learning system are obtained, namely the internet signal is often weak so that it is slow to access search pages on google and student learning facilities are still limited.